2017
DOI: 10.1136/thoraxjnl-2017-210217
|View full text |Cite
|
Sign up to set email alerts
|

Return to work and lost earnings after acute respiratory distress syndrome: a 5-year prospective, longitudinal study of long-term survivors

Abstract: Across 5-year follow-up, nearly one-third of previously employed ARDS survivors never returned to work. Delayed return to work was associated with patient-related and intensive care unit/hospital-related factors, substantial lost earnings and a marked rise in government-funded healthcare coverage. These important consequences emphasise the need to design and evaluate vocation-based interventions to assist ARDS survivors return to work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
4
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 42 publications
2
95
4
3
Order By: Relevance
“…Nevertheless, the fact remains that nearly 50% of patients were unemployed, which may have resulted in family problems and loss of substantial earnings. A 5-year follow-up of ARDS survivors showed that nearly one-third of previously employed ARDS survivors had never returned to work [33].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the fact remains that nearly 50% of patients were unemployed, which may have resulted in family problems and loss of substantial earnings. A 5-year follow-up of ARDS survivors showed that nearly one-third of previously employed ARDS survivors had never returned to work [33].…”
Section: Discussionmentioning
confidence: 99%
“…Despite burgeoning interest in post-ICU outcomes, there remains an incomplete understanding of the epidemiology of delayed return to work after critical illness, including longitudinal trends, associated factors and lost earnings. Recent studies in previously employed survivors of critical illness found that 67% and 69% returned to work at 12 and 60 months, respectively, and more than 70% accrued substantial lost earnings 4 5. In order to better understand the effects of critical illness on return to work, we conducted a systematic review and meta-analysis of studies evaluating return to work following ICU hospitalisation in survivors of critical illness.…”
Section: Introductionmentioning
confidence: 99%
“…Recovery after ICU discharge among ARDS patients is an important challenge [22]. In fact, studies have shown that most ARDS survivors have lost their previous job and never resume employment post-discharge [23,24]. Critically ill patients in the United States who do not have health insurance receive fewer critical care services and may experience worse clinical outcomes [25].…”
Section: Discussionmentioning
confidence: 99%